Crise Sanitária e (Des) Coordenação Federativa: impactos nas políticas sociais à população idosa em estados nordestinos durante a COVID-19 - Leite, Vyna Maria Cruz (2025)
This thesis is part of the debate on decisions and strategies for health care and defense of the rights of the elderly population, taken in the context of the political and health crisis of the COVID-19 pandemic. We proposed to analyze health care for this population considering intergovernmental relations during the Bolsonaro government. The research adopted a multi-method approach, using the nine states of the Northeast as the empirical field. Demographic data, morbidity and mortality, number of cases and deaths from COVID-19, hospitalizations, and vaccination were used. State decrees of social distancing and the start of vaccination for the elderly population were analyzed, comparing the states of the region. The 24 Bulletins of the Scientific Committee of the Northeast Consortium, published between April 2020 and April 2022, and the analysis of ten interviews with managers of health and social assistance policies in Ceará, Rio Grande do Norte, and Paraíba were also used. The results indicate that morbidity and mortality among the elderly population was already high before the pandemic, but showed a sharp increase after the health emergency, affecting all states in the region. There was relative homogeneity in the measures adopted by state governments to face the crisis, as well as a significant increase in hospitalizations and deaths from COVID-19, even after the implementation of strict contingency measures and the start of vaccination. The federal crisis intensified due to the lack of national coordination, particularly with regard to care for the elderly population, boosting interstate cooperation in the Northeast region. However, state initiatives, although relevant, proved insufficient to fully mitigate the impacts of the pandemic on this vulnerable group. The denialism and discontinuity of the Federal Government in relation to the coordination model resulted in the fragmentation and ineffectiveness of responses, with especially severe repercussions for the elderly population. In contrast, the northeastern states have structured collaborative strategies with different levels of power, prioritizing cooperation over conflict. We conclude that the planning and implementation of new policies aimed at guaranteeing the rights of the elderly population, as well as the strengthening of institutional mechanisms that prevent federative disarticulation, especially in crisis situations, are still necessary.